Measurement of the bending elastic modulus in unilamellar vesicles membranes by fast field cycling NMR relaxometry. (December 2016) - Dominguez, Gabriela A.; Perlo, Josefina; Fraenza, Carla C.; Anoardo, Esteban
Graphical abstract: Highlights: The bending elastic modulus of liposome membranes can be measured using field-cycling NMR relaxometry. A simplified method using limiting experimental conditions is discussed. Data could be successfully reduced using a simplified model. Obtained values of the elastic modulus are consistent with other studies. DMPC + cholesterol mixtures were used at different concentrations. Abstract: The elastic properties of lipid membranes can be conveniently characterized through the bending elastic modulus κ. Elasticity directly affects the deformability of a membrane, morphological and shape transitions, fusion, lipid-protein interactions, etc. It is also a critical property for the formulation of ultradeformable liposomes, and of interest for the design of theranostic liposomes for efficient drug delivery systems and/or different imaging contrast agents. Measurements of κ in liposome membranes have been made using the fast field cycling nuclear magnetic relaxometry technique. We analyze the capability of the technique to provide a consistent value of the measured quantity under certain limiting conditions. Relaxation dispersions were measured acquiring a minimal quantity of points, within a reduced Larmor frequency range and, under inferior experimental conditions (in the presence of magnetic field in-homogeneity and lower power supply stability). A simplified model is discussed, showing practical advantages when fitting the data within the reduced frequency range. Experiments are contrasted with standard measurements performed in a state-of-the-art relaxometer. The methodology was tested in samples of 1, 2-dimyristoyl- sn -glycero-3-phosphocholine with different percentiles of cholesterol. We observe a tendency to a decrease in κ with increasing temperature, and a tendency to increase with the cholesterol percentile.